Pengaruh Latihan Resistance Band Dan Medicine Ball Terhadap Servis Atas Pada Siswa Ekstrakurikuler Bola Voli Di MTS Istiqomah Salumakarra - Muh Yahya; Ahmad Ahmad; Jusriati Jusriati (Universitas Hamzanwadi, 2026)
Overhead serving ability in volleyball is influenced by arm muscle strength and power. However, extracurricular volleyball students at MTS Istiqomah Salumakarra still experience limitations in mastering this technique. This study aims to analyze the effect of Resistance Band and Medicine Ball exercises on overhead serving ability, as well as to compare the effectiveness of these two exercise methods. The method used was an experiment with a two-group pretest-posttest design. The sample consisted of 20 male students who were divided into two groups randomly. The research instrument was an overhand serve test that had been tested for validity and reliability. The data were analyzed using a paired sample t-test and an independent sample t-test with a significance level of α = 0.05. The results showed that: (1) Resistance Band training had a significant effect on improving overhead serves (t = 18.974; p = 0.000), (2) Medicine Ball training also had a significant effect (t = 11.781; p = 0.000), and (3) There is a significant difference between the two methods, where Medicine Ball is more effective than Resistance Band (p = 0.031). The conclusion of this study is that although both exercises improve overhead serve ability, Medicine Ball exercises provide a more optimal impact on the development of serve power and accuracy.